Humour in Meetings: A Case Study of Power in the Malaysian Academic Context - Mohd Omar, Nor Azikin; Mohd Jan, Jariah (2013)
The conceptualisation of humour as a means of communication is not new (Martineau, 1972, p. 101). Research on the social functions of humour has contributed valuable information not only on the positive psychological effect of humour, but also on the understanding of social interaction patterns and the dynamics of group structure (Martineau, 1972, p. 103). Studies from the West have indicated that humour is highly recognised as a powerful discourse to be used to wield power in workplace setting (Sollit-Morris, 1997; Holmes & Marra, 2002a; Holmes & Stubbe, 2003; Arfeen, 2009). This study investigates the functions of humour and the enactment of power amongst academics in asymmetrical relations. The parameters of this study are confined to the different status position of the participants who use humour to wield power during academic management meetings. Data for the study were collected from semi-formal meetings that were recorded in a local university in the state of Terengganu. The instances of humour elicited from the naturally-occurring discourse of the academic staff were categorised based on Hay’s Taxonomy of Functions of Humour (1995), which mainly focuses on power in discourse. The findings revealed that the production of humour in academic management meetings is highly influenced by the status or position that one occupies.